The role of retrograde intraflagellar transport in flagellar assembly, maintenance, and function - Engel, Benjamin D. (The Rockefeller University Press, 2012)
The maintenance of flagellar length is believed to require both anterograde and retrograde intraflagellar transport (IFT). However, it is difficult to uncouple the functions of retrograde transport from anterograde, as null mutants in dynein heavy chain 1b (DHC1b) have stumpy flagella, demonstrating solely that retrograde IFT is required for flagellar assembly. We isolated a Chlamydomonas reinhardtii mutant (dhc1b-3) with a temperature-sensitive defect in DHC1b, enabling inducible inhibition of retrograde IFT in full-length flagella. Although dhc1b-3 flagella at the nonpermissive temperature (34°C) showed a dramatic reduction of retrograde IFT, they remained nearly full-length for many hours. However, dhc1b-3 cells at 34°C had strong defects in flagellar assembly after cell division or pH shock. Furthermore, dhc1b-3 cells displayed altered phototaxis and flagellar beat. Thus, robust retrograde IFT is required for flagellar assembly and function but is dispensable for the maintenance of flagellar length. Proteomic analysis of dhc1b-3 flagella revealed distinct classes of proteins that change in abundance when retrograde IFT is inhibited.